GE_GERICHTE P/1826/2007 vom 14. August 2007 - GE Cour de justice (2007)
; OBLIGATION D'ENTRETIEN | reformatio in peius admise - condamnation à une peine pécunaire sans sursis | CP.217; CP.34; CP.42; CPP.242